Analisis Kemampuan Ekstrak Metanol Daun Bidara Indigenous Pulau Sumbawa Sebagai Pengawet Ikan Nila: Analysis of Indigenous Sumbawa Bidara Leaf Extract as Preservative for Tilapia Fish - Nairfana, Ihlana; Murtawan, Heri; Fatimah, Nurul (Jurnal Teknologi dan Mutu Pangan, 2023)
Tilapia (Oreochromis niloticus) is one type of freshwater fish that has good prospects for development. Mentioning one of the weaknesses of tilapia is that it is easy to experience a decrease in freshness, microorganism activities that occur in fish or the presence of fat oxidation processes that cause damage and deterioration in quality in fish. Bidara (Ziziphus mauritiana) leaves contains, alkaloids, flavonoids, phenols, tannins and saponins so that they can be used as natural preservatives for fish because of the activity of flavonoids and phenols found in bidara leaves can be used as antimicrobial and natural preservatives. The purpose of this study was to determine the effect of bidara leaf methanol extract on the quality of tilapia freshness and tilapia microbiology. This study used 2 methods, organoleptic results using empirical methods with methanol extract concentrations of bidara leaves 0%, 5%, 10% and 15%, while bacterial tests used the TPC (Total Plate Count) method. Based on the results of the study showed that the methanol extract of bidara leaves was able to maintain the quality of tilapia freshness based on the appearance of the eyes, gills, mucus, meat, aroma and texture and the number of microbes. The best treatment is a 5% extract concentration that is able to maintain the freshness of the fish for up to 9 hours. Total cell during storage of 3 hours, 6 hours and 12 hours are still included in the SNI requirements, which is no more than 5.0 x 105 cell/g.